Presidents' Secret Wars : CIA and Pentagon Covert Operations From World War II Through Iranscam - Prados, John (New York William Morrow, 1988)
Provides an analysis of postwar covert activities by United States intelligence agencies, documenting the early days of the CIA and its operations.
John Prados adds his concluding findings on US covert operations in Angola, Afghanistan, Nicaragua & the Persian Gulf. Acclaimed as a landmark book about US intelligence agencies in the postwar era, Presidents' Secret Wars describes the secret warfare mounted by the president, the CIA & the Pentagon--operations aimed at altering the destinies of nations & the course of global politics. Prados uses many newly declassified documents to open a vital window on this most secret aspect of American foreign policy.
Include Abbreviations, Acronyms, Notes, Bibliography and Index.
CIA and Pentagon covert operations from World War II through Iranscam.
Keywords: Military intelligence -- United States -- Diplomatic relations -- United States. Central Intelligence Agency -- Intelligence service -- Espionage, American -- Iran-Contra Affair (1985-1990)